UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA POKOK BAHASAN KLASIFIKASI MAKHLUK HIDUP DENGAN MENGGUNAKAN MODELPROBLEM BASED LEARNING DI KELAS VII A SMP NEGERI 4 TAPUNG HILIR - Nuryati Nuryati (Journal of Education and Teaching, 2020)
The design of this study uses classroom action research. Classroom Action Research. There are four stages in action research, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. In this study, researchers conducted activities in two cycles with each cycle consisting of one meeting. The results of this study describe students' learning outcomes data on the subject Classification of Living Things by using the Problem Based Learning model on Class VII A students of SMP Negeri 4 Tapung Hilir. Data collected by researchers from the learning outcomes of students through written tests. From the results of the assessment conducted in the first cycle that is obtained a value of 50-56 with a frequency of 2 (10%), a value of 57-63 with a frequency of 4 (20%), a value of 64-70 with a frequency of 4 (20%), a value of 71-77 with a frequency of 5 (25%), a value of 78-85 with a frequency of 5 (25%). From the results of the assessment conducted in the second cycle that is obtained a value of 65-71 with a frequency of 2 (10%), a value of 72-78 with a frequency of 3 (15%), a value of 79-85 with a frequency of 6 (30%), a value of 86-92 with a frequency of 3 (15%), a value of 93-100 with a frequency of 6 (30%). Based on the data obtained in Cycle I shows that the number of students who completed as many as 10 students or (50%), not complete as many as 10 students or (50%), while the second cycle of students who completed as many as 17 students or (85 %), and incomplete 3 students or (15%).